Comparison of hemodynamic responses to orotracheal intubation with Tuoren video laryngoscope and Macintosh direct laryngoscope in adult hypertensive patients - Debjani Gayen; Mandal, Sangita; Debojyoti Das; Chakraborty, Soma; Sarfraaz Rahman; Roy, Palash; Mohanchandra Mandal (Asian Journal of Medical Sciences, 2024)
Background: Laryngoscopy and intubation lead to unfavorable hemodynamic responses. Many studies have already compared direct laryngoscope (DL) and different types of video laryngoscopes (VLs). While some of those reported favorable response with use of VL, others have depicted an unfavorable response with VL. Aims and Objectives: Hence, the present study was carried out to compare the hemodynamic response to laryngoscopy between use of Macintosh DL and Tuoren VL in controlled hypertensive patients during elective surgery. Materials and Methods: A total of 122 patients were recruited for this interventional study. Patients were allocated into two groups to have their intubation with Tuoren VL (Group V, n=61) or Macintosh DL (Group D, n=61). The mean arterial pressure (MAP) at 1 min after intubation was the primary outcome. Other outcome measures were to compare heart rate (HR) at different time points, procedure time (glottis exposure time and intubation time), and number of attempts. Results: The use of DL led to considerably higher MAP at 1, 3, and 5 min after laryngoscopy and intubation compared with VL. However, comparable HRs were found between the two groups at such time points. Glottis visualization time and intubation time were considerably higher using VL compared with DL. The mean total procedure time was considerably lesser with DL over VL (mean, 29.5 vs. 38.5 s, respectively, <0.001). Conclusion: Tuoren video laryngoscope can be a better alternative to Macintosh direct laryngoscope in view of considerably lesser rise of mean arterial pressure and comparable heart rate during laryngoscopy and intubation in hypertensive patient.